Crossing Boundaries: The Cultural and Geographic Passage of Olaudah Equiano - Sharma, Kamal; Joshi, Amrit Prasad (Bon Voyage, 2025)
This article explores the cultural and geographic crossings undertaken by Olaudah Equiano as portrayed in his seminal autobiography The Interesting Narrative and Other Writings. As an African man kidnapped and enslaved, he experienced a cruel form of transatlantic slavery. In this regard, the study analyzes Equiano’s navigation of different worlds and transatlantic experiences and complexities of identity formation in relation to slave identity. His movement from Nigeria, Caribbean and Verginia, though forced one, gives him opportunities to learn multiple customs and culture. Along with charting the physical displacements, the narrative underscores Equiano’s evolving cultural identity while passing through multiple social, linguistic and religious contexts. The issue of crossing physical, psychological, religious and cultural boundaries in the journey is the chief concern of the paper. The questions- “Does the crossing help him form an identity? Is cultural adaptability of alien communities necessary for survival in the servitude?’- are main concerns of the study. This is a qualitative research having textual analysis as its method employed in the study. The travel theoretical insights; struggle and resilience required to cross boundaries are used in relation to the text under study. Equiano, while crossing a numerous geographical boundaries, continues to travel extensively, mapping multiple nations and measuring the different societies along with the harsh realities of slavery and selfhood. Thus, this paper provides an approach of forced travel to servitude travel in the cultural and geographic passage where the traveller finds sense of ‘Self’ in the painful travelogue through double consciousness hinting two-ness – a sense of identity shaped by native culture and another by dominant culture where native people reach either through forced travel or through self-desired effort.